Cover Feature: A Route to Synthesize MgAl‐Layered Double Hydroxides via Topotactic Reaction of Mg2+ with Al(OH)3 (Eur. J. Inorg. Chem. 25/2018). Issue 25 (13th June 2018) - Li, Yanan; Liang, Dujuan; Feng, Pingping; Yang, Xiaojing
Abstract : The Cover Feature shows the alteration process of Al(OH)3 solid/crystals, bottom left, to MgAl‐LDH crystals, around the crystals of Al(OH)3 toward the top right, in an aqueous solution containing Mg 2+, OH –, and NO3 – ions (the blue area around the crystals). The alteration involves the insertion of Mg 2+, OH –, as well as interlayer species including NO3 – in the solution, into the solid and the migration of Al 3+ ions in the solid. The topotactic reaction mechanism is thus illustrated in the picture. More information can be found in theCommunication by X. Yang et al.